Nigeria's Shi'a Islamic Movement and Evolving Islamist Threat Landscape: Old, New and Future Generators of Radicalization. Issue 2 (3rd April 2019) - Gray, Simon; Adeakin, Ibikunle
ABSTRACT: The Islamic Movement in Nigeria (IMN) emerged in the early 1980s as the first Shi'a Islamist organization in Nigeria. However, since the early-2000s this organization has become increasingly confrontational and, at times, violent towards the Nigerian state. Through a qualitative analysis of four key theories concerning the causal dynamics of Islamist radicalization, this article argues that contextual and ideological factors, local and global, generated and radicalized the IMN. These include historical factors, the collapse of the First Republic (1960-1966), military rule, Sunni-Shi'a tensions, the spread and intensification of radical and extremist Islamist ideologies and actors in post-independence Nigeria, and state repression. These factors represent what this study refers to as "old" and "new" generators responsible for the rise and subsequent radicalization of the IMN to date. It concludes with the prognosis that if these generators endure, or worsen, the IMN is likely to undergo a "future", more violent phase of radicalization that may trigger a full-blown Shi'a insurgency with potential backing from the Iranian regime, in particular via the Quads force and/or Hezbollah.